Bilateral Mandibular Premolar Dens Invaginations: A Case Report. (9th October 2012) - Holliday, Richard; Beecroft, Emma
Abstract : Dens invaginations are a rare developmental defect most commonly affecting maxillary lateral incisors, with very few reported cases in mandibular teeth. We describe a rare case of bilateral first mandibular premolar dens invaginations type I, where apparently health teeth presented with periapical pathology.